Serological Influences on Dry Eye: Insights from the Sjögren's International Collaborative Clinical Alliance - Chloe Shields, BS; Pragnya Rao Donthineni, MD; Rohit Muralidhar, BS; Shreya Bhatt, MS; Ema V. Karakoleva, BS; Alan Baer, MD; Robert Fox, MD; Sara S. McCoy, MD, PhD; Anat Galor, MD, MSPH (Ophthalmology Science)
Purpose: To define associations between serologies, specifically Sjögren syndrome–related antigen A (SSA) antibody and immunoglobulin (Ig) levels, on ocular profiles in patients enrolled in the Sjögren's International Collaborative Clinical Alliance (SICCA) cohort. Design: A retrospective cohort study. Subjects: Individuals from the SICCA cohort (n = 3514). Methods: A retrospective analysis to examine relationships between dry eye (DE) symptoms and signs and serologic status, including SSA (SSA+ Sjögren disease [SjD], SSA− SjD, non-SjD) and Ig (G, A, M) levels (low, normal, and high). Main Outcome Measures: Univariate analyses using analysis of variance and chi-square tests examined differences in ocular profiles by serologies. Multivariable analyses were then performed to account for potential confounding variables, including other serological measures. Results: The mean age of the SICCA cohort was 53 ± 13 years, with the majority identifying as female (91%, n = 3185) and White (54%, n = 1894). The presence of SSA impacted ocular profiles, with the SSA+ SjD group reporting less severe symptoms compared with the SSA− SjD and non-SjD groups (spontaneous pain: 2.61 ± 2.83 vs. 3.39 ± 3.01 vs. 3.52 ± 3.09, P < 0.001), but more frequently having ocular signs (low tear production: 57% vs. 52% vs. 28%, P < 0.001; ocular surface staining [OSS]: 83% vs. 69% vs. 35%, P < 0.001). Immunoglobulin levels showed a similar pattern, with the high IgG level group reporting less severe ocular symptoms in the SjD (spontaneous pain: 2.41 ± 2.82 vs. 3.10 ± 2.91 vs. 3.40 ± 2.96; P < 0.001 and P < 0.05) and non-SjD (spontaneous pain: 2.09 ± 2.35 vs. 3.58 ± 3.11 vs. 3.85 ± 3.11; P < 0.001) groups but more severe signs (SjD group: low tear production: 60% vs. 53% vs. 49%; OSS: 88% vs. 72% vs. 70%; P < 0.001) compared with the normal and low-level groups. A similar pattern was noted for IgA levels. Most associations remained significant when considered concomitantly. Conclusions: Ocular manifestations of DE are influenced by serological factors. Specifically, SSA+ and high IgG and IgA status align with a disease picture of clinical signs of DE disease out of proportion to pain symptoms, while SSA− and low and normal IgG and IgA status align with a DE disease picture of symptoms that outweigh signs. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.